CONTROL OF FUSARIUM WILT DISEASE IN ONION PLANTS (Allium Ascolonicum) USING TRICHODERMA BIOFUNGICIDE - Rachmawati, Diding; Korlina, Eli; Baswarsiati, Baswarsiati (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2020)
One of the obstacles by farmers at each planting season is the high pests and diseases, but the control of pests and diseases is done using chemical pesticides. It is therefore necessary to find an alternative to chemical pesticides by using biopesticides. The assessment carried out in the laboratory of Pests and Diseases IAAT East Java to create Trichoderma powder. Assessment of field experiments conducted in the garden Karangploso Starting in January-May 2014, varieties Super Philip, a randomized block design with five treatments, each treatment was repeated three times, the treatment consists of (A) Trichoderma powder dose of 1 g / l , (B) Trichoderma powder dose of 2 g / l , (C) Trichoderma powder dose of 3 g / , (D) Pro chip the recommended dose (5g / 40 l) , (E) Controls. The assessment aims to the effectiveness of Trichoderma powder doses in controlling fusarium wilt. Results showed that root length, number of tillers per hill and wet weight per plot obtained the highest in treatment C (Trichoderma powder dose of 3 g / l) respectively by 9.15 cm and 8.63 kg 12.16 tillers, Trichoderma powder treatment dose 1-3 g / l had no effect on plant height and leaf number equivalent to the Pro chip application the recommended dose (5g / 40 l , the percentage of fusarium wilt disease attacks the lowest obtained in treatment C (Trichoderma powder dose of 3 g / l).